2022
DOI: 10.1101/2022.07.26.501417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic plasticity cooperates with emergent cell-cell interactions to drive neoplastic tissue remodeling in the pancreas

Abstract: The response to tumor-initiating inflammatory and genetic insults can vary amongst morphologically indistinguishable cells, suggesting yet uncharacterized roles for epigenetic plasticity during early neoplasia. To investigate the origins and impact of such plasticity, we perform single-cell analyses on normal, inflamed, pre-malignant and malignant tissues in autochthonous models of pancreatic cancer. We reproducibly identify heterogeneous cell-states that are primed for diverse late-emerging neoplastic fates a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…The simultaneous profiling of transcriptomes and chromatin accessibility has been a standard technology to elucidate epigenetic regulations of transcriptional processes [6, 36]. Several studies have shown that chromatin accessibility changes prior to changes in gene expression [4, 36].…”
Section: Resultsmentioning
confidence: 99%
“…The simultaneous profiling of transcriptomes and chromatin accessibility has been a standard technology to elucidate epigenetic regulations of transcriptional processes [6, 36]. Several studies have shown that chromatin accessibility changes prior to changes in gene expression [4, 36].…”
Section: Resultsmentioning
confidence: 99%